Unipolar pedicled latissimus dorsi transfer for elbow reanimation in traumatic brachial plexus injuries - Agrawal, Neeraj K.; Choudhary, Aditya N.; Agrawal, Preeti (International Journal of Research in Medical Sciences, 2020)
Background: Brachial plexus injuries are troubling for the patients socially, economically and emotionally. Elbow joint being a large and vital joint needs to be reanimated so that the patient can carry out his routine work and bring the hand to the mouth. Number of procedures have been defined but latissimus dorsi being a large muscle is the muscle of choice for transfer in cases who present late. Bipolar latissimus dorsi transfers have often been reported but unipolar latissimus dorsi transfer has also been described. Authors have studied the unipolar muscle transfer, it’s surgical technique and results. Methods: In this study 18 patients were studied for demographic data, pre- and post-operative flexion of the elbow and the MRC grade of the corresponding movements. Diagnostic work up in the form of nerve conduction velocity, electromyography and magnetic resonance imaging were carried out and evaluated for their significance in traumatic brachial plexus injuries. Results: In this study 13 patients had avulsion of the C5-6 roots on magnetic resonance imaging. The patients presented after a period of 128.83±56.76 days. Substantial time elapsed and ruled out primary brachial plexus reconstruction or nerve transfers. The average elbow flexion improved from 6.67±5.69 degrees (range: 0-20 degrees) to 86.94±12.38 degrees (range: 65-110 degrees) following unipolar latissimus dorsi transfer. 12 patients (66.67%) developed M4 or M4+ power. Conclusions: Unipolar latissimus dorsi muscle transfer is a reliable method and most of the patients develop adequate strength and satisfactory function at the elbow joint.